2021
DOI: 10.1111/acel.13428
|View full text |Cite
|
Sign up to set email alerts
|

Single‐oocyte transcriptome analysis reveals aging‐associated effects influenced by life stage and calorie restriction

Abstract: Chromosome segregation errors in oocytes lead to the production of aneuploid eggs, which are the leading cause of pregnancy loss and of several congenital diseases such as Down syndrome. The frequency of chromosome segregation errors in oocytes increases with maternal age, especially at a late stage of reproductive life. How aging at various life stages affects oocytes differently remains poorly understood. In this study, we describe aging‐associated changes in the transcriptome profile of mouse oocytes throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…The development of omics provides a basis for an in-depth understanding of molecular changes in cells [ 44 ]. Transcriptome analysis of cumulus cells and oocytes revealed molecular pathways involved in reproductive aging physiology [ 45 ], such as cases where the combined analysis of cumulus cells and oocyte transcriptome sequencing revealed age-related effects influenced by life stage and calorie restriction [ 46 ]. Our study used Smart-seq 2 and RNA-seq for transcriptome sequencing in oocytes and cumulus cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of omics provides a basis for an in-depth understanding of molecular changes in cells [ 44 ]. Transcriptome analysis of cumulus cells and oocytes revealed molecular pathways involved in reproductive aging physiology [ 45 ], such as cases where the combined analysis of cumulus cells and oocyte transcriptome sequencing revealed age-related effects influenced by life stage and calorie restriction [ 46 ]. Our study used Smart-seq 2 and RNA-seq for transcriptome sequencing in oocytes and cumulus cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used Smart-seq 2 and RNA-seq for transcriptome sequencing in oocytes and cumulus cells, respectively. According to the relevant reports of Mishina’s use of hub genes [ 46 ], we found the top ten GSEA pathways and top ten hub genes of oocytes and cumulus cells. A combined analysis of the omics data showed that the cytokine–cytokine receptor interaction in the top ten GSEA pathways displayed abnormalities in both aging cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the contemporary surrounding GCs had much lower CHD7 expression levels. In another single-cell RNAseq analysis evaluating the expression levels of Chd7 in mouse oocytes and the surrounding cumulus at different ages, we obtained data showing high Chd7 expression levels in mouse GV oocytes at 2, 9, and 14 months old from GSE159281 (Figure 1B) (25).…”
Section: High Expression Levels Of Chd7 In Human and Mouse Oocytesmentioning
confidence: 99%
“…Melatonin, a strong antioxidant, can increase telomere length and reduce inflammation during ovarian aging (Secomandi et al, 2022). Calorie restriction can also prevent aging-associated oocyte aneuploidy (Mishina et al, 2021). In addition, developments in mitochondrial replacement therapy, nuclear genome transfer, and autonomous germline mitochondrial energy transfer (AUGMENT) techniques improve oocyte quality (Reddy et al, 2015;Woods and Tilly, 2015), however clinical safety considerations require further evaluation (Tvrdá et al, 2021).…”
Section: The Molecular Mechanisms Underlying Age-associatedmentioning
confidence: 99%